2006
DOI: 10.1002/pros.20340
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of tumor-reactive transforming growth factor-beta insensitive CD8+ T cells into the tumor parenchyma is associated with apoptosis and rejection of tumor cells

Abstract: Our results demonstrate the mechanism of anti-tumor effect of tumor-reactive TGF-beta-insensitive CD8+ T cells that adoptive transfer of these CD8+ T cells resulted in infiltration of these immune cells into the tumor parenchyma, secretion of relevant cytokines, and induction of apoptosis in tumor cells. These results support the concept that tumor-reactive TGF-beta-insensitive CD8+ T cells may prove beneficial in the treatment of advanced cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…38 Similarly, ex vivo-expanded tumor-antigen-specific TGFbinsensitive CD8 þ T cells, when adoptively transferred into recipient mice with established pulmonary tumors, were able to contain tumor growth and limit tumor metastasis; an effect which correlated with elevated IFNã serum concentrations. 39 These findings, along with the lymphoproliferative disorders observed in mice deficient in TGFb1 15,40 or in mice with CD8 þ T cells-expressing dnTGFRII, 41 confirm the role that TGFb signaling has in controlling T-cell proliferation, thus maintaining T-cell homeostasis.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…38 Similarly, ex vivo-expanded tumor-antigen-specific TGFbinsensitive CD8 þ T cells, when adoptively transferred into recipient mice with established pulmonary tumors, were able to contain tumor growth and limit tumor metastasis; an effect which correlated with elevated IFNã serum concentrations. 39 These findings, along with the lymphoproliferative disorders observed in mice deficient in TGFb1 15,40 or in mice with CD8 þ T cells-expressing dnTGFRII, 41 confirm the role that TGFb signaling has in controlling T-cell proliferation, thus maintaining T-cell homeostasis.…”
Section: Discussionmentioning
confidence: 65%
“…However, if these T cells were engineered to express dnTGFRII then most of the tumors were eradicated. 39 Similarly, established syngeneic lymphomas and melanomas regressed in Rag-/-mice that had been reconstituted with TGFb-insensitive CD8 þ T cells. Tumor eradication depended on CD4 þ T cells, and in contrast to the previous study, 39 tumors were only eradicated completely when T cells were transferred no later than 3 days after tumor inoculation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Soluble betaglycan administered as a protein or ectopically expressed, inhibited TGF-β signaling and angiogenesis, and reduced tumor growth and lung metastases in a number of mouse tumor models (Andres et al, 1989;Bandyopadhyay et al, 2002;Finger et al, 2008;Naumann et al, 2008). Expression of a dominant-negative (dn) TβRII with an inactive truncated kinase has also demonstrated anti-tumor activity in pre-clinical models (McEarchern et al, 2001;Zhang et al, 2006;Qin et al, 2008)., Some studies of dn-TβRII, however, demonstrated enhancement of tumor growth raising safety concerns about this approach (Tang et al, 2003;Huntley et al, 2004). As of yet, none of these agents has entered clinical trials.…”
Section: Soluble Tβrii-f C Fusion Proteins and Soluble Tβriii (Betaglmentioning
confidence: 99%
“…In lung carcinoma patients, increasing numbers of TILs have also been shown to significantly improve disease-specific survival (Al-Shibli et al, 2008). PCa glands are also frequent diffusely infiltrated (CD4+T-cells as if CD8+T-cells) so suggesting that PCa may be immunogenic but the correlation of these findings to clinical data is not that clear as in other tumor entities (McArdle et al, 2004;Zhang et al, 2006). Altogether, these observations support the immunosurveillance hypothesis and form the rationale to use the immune system to control tumor burden by vaccine-based interventions against cancer relying on the stimulation of an effective antitumor immune response in the cancer patient and resulted recently in labelling "avoiding immune destruction" as an emerging hallmark of cancer by the scientific community (Hanahan & Weinberg, 2011).…”
Section: Introductionmentioning
confidence: 99%